In Situ Proliferating Peptide Nanoparticle Augments Multi‐Target Intervention of Secondary Brain Damage Following Subarachnoid Hemorrhage - Yibin Zhang; Peisen Yao; Fuxiang Chen; Shufa Zheng; Xuegang Niu; Haojie Wang; Yuanxiang Lin; Bin Gao; Dezhi Kang (Advanced Science)
Abstract Subarachnoid hemorrhage (SAH), a lethal stroke subtype, involves complex pathological cascades triggered by neuro‐glial units for persistent neuroinflammation, oxidative damage and programmed neuronal cell death. Single‐target and traditional multi‐target therapies, derived from individual drugs, show limited efficacy in addressing these interconnected events, due to spatiotemporal heterogeneity of action in single‐target components. This highlights the urgent need for not only new therapeutic targets, but advanced multi‐target drugs. Herein, we identify elevated cell‐free DNA (cfDNA), a key neuroinflammatory driver, as correlated with SAH severity and poor prognosis, suggesting its therapeutic potential. Furthermore, a novel “in situ proliferation” strategy is proposed and a flexible multi‐target peptide nanoparticle is developed through co‐assembling matrix metalloproteinase‐2 responsive cationic peptide and glutathione peroxidase‐mimicking peptide (GPXP). Upon reaching injury lesions, this system splits into two individual drugs: cationic peptide scavenges pathological cfDNA and inhibits microglia‐mediated neuroinflammation, while GPXP protects neurons against oxidative damage and neuronal apoptosis/ferroptosis. Consequently, this strategy proves superior therapeutic effects on reducing secondary brain injury and promoting neurofunctional recovery in SAH mice. These findings not only highlight the essential role of cfDNA in SAH but offer a flexible resolution to advance multi‐target combinational therapy.